Influenza and Bacterial Pathogen Coinfections in the 20th Century - Xuan-Yi Wang; Paul E. Kilgore; Kyung Ah Lim; Song-Mei Wang; Jeongseok Lee; Wei Deng; Mei-Qi Mo; Batmunkh Nyambat; Jing-Chen Ma; Michael O. Favorov; John D. Clemens (Interdisciplinary Perspectives on Infectious Diseases)
To help understand the potential impact of bacterial coinfection during pandemic influenza periods, we undertook a far-reaching review of the existing literature to gain insights into the interaction of influenza and bacterial pathogens. Reports published between 1950 and 2006 were identified from scientific citation databases using standardized search terms. Study outcomes related to coinfection were subjected to a pooled analysis. Coinfection with influenza and bacterial pathogens occurred more frequently in pandemic compared with seasonal influenza periods. The most common bacterial coinfections with influenza virus were due to S. pneumoniae, H. influenzae, Staphylococcus spp., and Streptococcus spp. Of these, S. pneumoniae was the most common cause of bacterial coinfection with influenza and accounted for 40.8% and 16.6% of bacterial coinfections during pandemic and seasonal periods, respectively. These results suggest that bacterial pathogens will play a key role in many countries, as the H1N1(A) influenza pandemic moves forward. Given the role of bacterial coinfections during influenza epidemics and pandemics, the conduct of well-designed field evaluations of public health measures to reduce the burden of these common bacterial pathogens and influenza in at-risk populations is warranted.